Forming limit diagrams - Issa, Jimmy (2004)
In this work, the Marciniak and Kuczynski model (MK) will be reviewed and will be generalized to a more general approach for the calculation of forming limit diagrams. In the new model we will account for all directions of the imperfection. This new approach has been used to calculate the theoretical FLDs (forming limit diagrams) for Vonmises, Barlat Yield96 and Barlat Yield2000 for aluminum alloy Al2008-T4 and compared with an experimental one. All the derivations needed for the implementation of the code are derived in the appendix for all yield functions. Finally the stretch stamping test will be modeled using LS-DYNA. A very good agreement has been achieved between the experimental and theoretical results.